Inorganic nitrogen dynamics of throughfall following fertilization in a red pine stand. Issue 4 (2nd October 2017) - Kim, Choonsig; Baek, Gyeongwon; Park, Seong-Wan; Kim, Seongjun
ABSTRACT: Inorganic nitrogen fluxes caused by rainfall and throughfall following fertilizer applications were measured in a red pine stand located in the Wola National Experimental Forest in Jinju, Korea. Fertilizer (N3 P4 K1 = 113:150:37 kg ha −1 yr −1 ) was applied for 2 years, and inorganic nitrogen fluxes were monitored from April 2011 to March 2013. Monthly variations in inorganic nitrogen concentrations were generally higher in the throughfall than in the rainfall, whereas monthly variations in concentrations were similar between the fertilized and control treatments. The mean NH4 + and NO3 − concentrations during the study period were 0.39 and 0.21 mg L −1 for the rainfall, 1.06 and 1.06 mg L −1 for the control, and 1.01 and 0.89 mg L −1 for the fertilizer treatments, respectively. Inorganic nitrogen fluxes were generally higher during the growing season (May–October) than during the dormant season (November–April). Inorganic nitrogen fluxes were higher in the throughfall (17.03 kg ha −1 yr −1 in the control treatments and 14.93 kg ha −1 yr −1 in the fertilizer treatments) than in the rainfall (10.66 kg ha −1 yr −1 ). This result indicates that inorganic nitrogen concentrations and fluxes of throughfall are affected by the amount of throughfall rather than by fertilizer application in a red pine stand.